A Note on the Returns to Human Capital in the Eighties: Evidence from Twelve Countries - Wilhelm Lorenz; Joachim Wagner; Karel van den Bosch (Luxembourg Income Study (LIS), 1990)
Based on identically specified human capital earnings functions of the Mincer-type, this paper reports estimates of the rates of return to human capital for full-time working male employees in twelve countries. The results are compared across countries and over time of the decade of the eighties.
Keywords: 330